Applied fluid mechanics - Papanastasiou, Tasos C. (Prentice Hall international series in the physical and chemical engineering sciences, 1994)
"This comprehensive volume enables readers to develop an understanding of the principles of fluid mechanics and to utilize problem-solving approaches for handling, transferring, and processing fluids." "Applied Fluid Mechanics emphasizes microscopic differential transport and lubrication type flows, which are essential in the emerging area of materials processing; covers hydrostatistics and capillarity, piping and hydraulics problems, meteorology and air pollution, materials processing, flows, thin film and coating flows, lubrication and stretching flows, and turbulent flows and mixing; presents step-by-step instruction reasoning and examples, providing a systematic approach to solving both macroscopic and microscopic problems; and offers convenient dual approaches to flow analysis, by control volume and by the Navier-Stokes equations."--BOOK JACKET.